Case report: Successful management of primary hyalinizing clear cell carcinoma in nasopharynx: a report of 2 cases and system analysis - Sun, Haiying; Yuan, Jie; Cheng, Qing; Hu, Juanjuan; Han, Nana; Yi, Lisha; Zhu, Yun (Frontiers in Oncology, 2024)
Hyalinizing clear cell carcinomas (HCCCs) are infrequent, malignant tumors characterized by their low-grade nature. They typically originate from minor salivary glands. However, these tumors can potentially emerge in any location with minor salivary glands, including the nasopharynx. This report presents two cases of HCCC in females aged 61 and 72 years, with both tumors approximately 4 cm in size. In the first case, a 72-year-old female presented with recurrent bilateral epistaxis. Imaging studies revealed a nasopharyngeal mass, surgically excised, and histopathological analysis confirmed HCCC. Postoperatively, the patient received combined chemotherapy and radiotherapy, achieving a recurrence-free status 2.5 years later.The second case involves a 61-year-old female with a two-year history of bloody nasal discharge. Imaging studies identified a nasopharyngeal lesion, surgically removed, and histopathological examination confirmed HCCC. This patient underwent radiotherapy followed by combination chemotherapy with paclitaxel and carboplatin, displaying no signs of recurrence upon reevaluation after 10 months. These cases highlight the successful management of HCCC through a comprehensive, multimodal approach, integrating surgical intervention and adjuvant therapy. The favorable outcomes emphasize the significance of a thorough treatment strategy for HCCC in the nasopharynx, providing valuable insights for clinicians. Further studies are essential to enhance our understanding of this rare entity and refine treatment protocols for optimized patient outcomes.